Anatomical and three-dimensional study of the abdominal vascular system in female rabbit using dissections and ultrasound - Aya A. Sulaiman; Rabab A. Naser; Ramadan A. Ahmed (Iraqi Journal of Veterinary Sciences)
Our aim is to provide reference data for the arterial diameter of abdominal arteries using ultrasound in healthy rabbits, which can be used to compare changes in arterial diameter in diseased rabbits or when performing experiments and creating a 3D model of abdominal arteries using casting material. The current study was conducted on ten domestic rabbits aged between 2-3 years and weighing 1-2 kg. Ultrasound examination of the abdominal wall was performed in the supine position. The results showed that the mean hepatic artery diameter for 1-1.5 kg was 0.25±0.04 cm while for 1.5-2 kg it was 0.37±0.07, and the mean renal artery diameter for 1-1.5 kg was 0.20±0.03 cm while for 1.5-2 kg it was 0.25±0.04. The ultrasound results indicated that the diameter of the blood vessels increases with weight gain. Anatomically, the rabbits were divided into two groups: the first group was injected with latex arteries, and the second group was injected with resin casting material. The results showed that the arteries of the first group were flexible. In contrast, the arteries of the second group were rigid and fragile and required more care in handling than the first group. The results indicated that latex injections help in accurate anatomical studies. In contrast, resin injections create a three-dimensional model of the arteries. We conclude that color Doppler ultrasound with a linear probe provides clear and accurate images of blood vessels, allowing doctors to accurately measure their diameter and assess blood flow within the vessels, thus helping to diagnose conditions such as atherosclerosis and arterial disease.